Who Is The Boss? De-Escalation of Commitment Strategy: Effectiveness of Share Responsibility and Superiors' Feedback An experimental investigation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research highlights the importance of understanding the negative effects of self-justification in organizational decision-making at the manager level. This article investigates the relationship between the influence of shared responsibility and feedback from superiors on commitment—the interaction between personal responsibility and superiors' input in the context of reinvestment decisions. Ninety-two student subjects were involved in this experiment. Experimental findings indicate that, although negative decision feedback has a more significant impact on increased commitment among managers, a positive framework has a more substantial effect on increased commitment among managers. When superiors' feedback is positive, decision-makers escalate their promise not to reinvest, even though reinvestments are not large. Meanwhile, when the supervisor's feedback is negative, it causes a considerable escalation of managers and managerial decision-makers reinvestments. We find that the de-escalation commitment (lower managers' self-justification) negatively impacts organizational decisions.